Produtividade de laranja correlacionada com atributos químicos do solo visando a zonas específicas de manejo - Costa, Nídia Raquel; Carvalho, Morel De Passos E [UNESP]; Dal Bem, Edjair Augusto [UNESP]; Dalchiavon, Flávio Carlos; Caldas, Rudgen Rodrigues [UNESP] (Escola de Agronomia/UFG, 2014)
Precision agriculture determines the exact crop management, based on the mapping of specific soil management zones. Thus, this study aimed to characterize the concept of specific soil management zone by using spatial correlations and ordinary cokriging between Valência orange yield and soil attributes, aiming to select the soil attribute that is more efficiently related to the increase in yield, in a geostatistical grid with 120 sampling points, in 1.65 ha. The soil attributes surveyed were: P, OM, pH, K+, Ca2+, Mg2+, H++Al3+, S, T and V%. The data were submitted to descriptive analysis, Pearson's correlations end geostatistical analysis. Thus, the orange yield resulted in significant ordinary cokrigings, for both the pH and soil Mg content evaluated. This technique allowed the creation of two specific zones of soil pH management closely associated to that yield. The obtaining of two specific management zones ratified the importance of precision agriculture, concerning the increased orange yield, because by keeping the two specific management zones obtained, the global yield of the area would be 16.91 t ha-1. However, by providing optimal conditions of soil pH to the one with the highest acidity level, it would be possible to obtain an increase of 7.58 t ha-1 in fruit yield, reaching the global average of 24.49 t ha-1.

A agricultura de precisão determina o exato manejo da lavoura, tendo como base o mapeamento de zonas específicas de manejo do solo. Assim, tentou-se caracterizar o conceito de zona específica de manejo do solo, pelo emprego de correlações espaciais, usando a cokrigagem ordinária entre a produtividade de laranja Valência e atributos do solo, objetivando selecionar o atributo do solo que mais eficientemente fosse relacionado com o aumento da referida produtividade, em malha geoestatística com 120 pontos amostrais, em 1,65 ha. Os atributos do solo pesquisados foram: P, MO, pH, K+, Ca2+, Mg2+, H++Al3+, S, T e V%. Foram aplicadas aos dados a análise descritiva, correlações de Pearson e análise geoestatística. Assim, a produtividade de laranja resultou em significativas cokrigagens ordinárias, tanto com o pH como com o teor de Mg do solo pesquisado. Essa técnica possibilitou a criação de duas zonas específicas de manejo do pH do solo intimamente associadas à referida produtividade. A obtenção de duas zonas específicas de manejo ratificou a importância da agricultura de precisão, frente ao aumento da produtividade de laranja, pois, mantendo-se as duas zonas específicas de manejo obtidas, a produtividade global da área seria de 16,91 t ha-1. Contudo, proporcionando-se condições ótimas de pH do solo àquela de maior acidez, poder-se-ia obter incremento de 7,58 t ha-1 na produtividade de frutos, alcançando a média global de 24,49 t ha-1.
Orange yield correlated with soil chemical attributes aiming specific management zones
Keywords: Citrus sinensis (L.) Osbeck; precision agriculture; geostatistics; soil management and conservation; Citrus sinensis (L.) Osbeck; agricultura de precisão; geoestatística; manejo e conservação do solo